PARENT INVOLVEMENT IN INSTILLING SOCIAL CARE ATTITUDES TO EARLY CHILDHOOD THROUGH THE FRIDAY BLESSING PROGRAM - Cipta Rumsari; Sri Nurhayati (IKIP Siliwangi Bandung, 2020)
This research aims to describe parents' involvement in instilling social care attitudes to early childhood through the Friday blessing program at PAUD Mawar Kota Bandung. The data collected in this study uses semi-structured interview techniques, participatory observations, and documentation studies. The method used is descriptive with a post positivistic approach with a simple research design. This study's respondents were a PAUD principal, two tutors, and two parents of PAUD Mawar students selected purposively. The results showed that parental involvement as a supporter, social agent, and streamline the program. While the factors inhibiting parental involvement are the busyness of parents and the lack of awareness of the importance of parental involvement in early childhood education programs. Friday Blessing Program in instilling social care in children is already underway judging by the participation of parents of students who participate in every activity carried out from preparation to implementation. Children's social care is instilled in a way that, together with parents and teachers, donate the dhuafa in the Friday Blessing program